The complete chloroplast genome of Aphelandra knappiae (Acanthaceae). Issue 1 (2nd January 2019) - Huang, Sunan; Deng, Yunfei; Ge, Xuejun
Abstract: Aphelandra knappiae is an important plant from the family Acanthaceae. The complete chloroplast genome of the genus Aphelandra was sequenced for the first time. The plastome of A. knappiae was 152, 457 bp in length. It consisted of a large single-copy (LSC) region (83861 bp) and a small single-copy (SSC) region (17, 888 bp), which were separated by two inverted repeats (IRs, 25, 354 bp). This plastome contained 114 unique genes, including 80 protein-coding genes, 30 tRNAgenes, and 4 rRNA genes. The overall GC content was 38.5%. Furthermore, phylogenetic analysis of five species in the Acanthaceae was also conducted. The whole chloroplast genome of this species will be useful for the future plant evolutionary, phylogeny and genomic studies in the family Acanthaceae.